Dielectric Properties of Two-Dimensional Bi2Se3 Hexagonal Nanoplates Modified PVDF Nanocomposites. (3rd July 2019) - Feng, Zunpeng; Hao, Yanan; Zhang, Jiameng; Qin, Jing; Guo, Limin; Bi, Ke
Abstract : Topological insulator two-dimensional (2D) Bi2 Se3 hexagonal nanoplates, which are highly insulating in the bulk and have a conductive topological surface state, have been prepared via an "EG- (ethylene glycol-) sol" method and characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Bi2 Se3 /PVDF (polyvinylidene fluoride) nanocomposites with various Bi2 Se3 contents have been fabricated by a tape-casting method. The microstructure and dielectric performance of the Bi2 Se3 /PVDF nanocomposites are studied. The dielectric constant of the dense nanocomposite films keeps a relatively low value of about 16 when the Bi2 Se3 content is lower than 12 vol.% then suddenly increases to 36 with a critical Bi2 Se3 content of 13 vol.% due to the percolation effect of the large aspect ratio of the 2D Bi2 Se3 nanoplates. The study of the Bi2 Se3 /PVDF nanocomposite system is conducive to the exploration of high-performance dielectrics.